Improvement of optimum pH and specific activity of pectate lyase from Bacillus RN.1 using loop replacement - Li, Piwu; Wei, Xiaofeng; Wang, Yun; Liu, Hui; Xu, Yanpeng; Zhang, Ziyang; Li, Junlin; Wang, Jianbin; Guo, Chuanzhuang; Sui, Songsen; Wang, Junqing; Wang, Ruiming (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Alkaline pectate lyase plays an important role in papermaking, biological refining and wastewater treatment, but its industrial applications are largely limited owing to its low activity and poor alkali resistance. Methods: The alkaline pectate lyase BspPel from Bacillus RN.1 was heterologously expressed in Escherichia coli BL21 (DE3) and its activity and alkali resistance were improved by loop replacement. Simultaneously, the effect of R260 on enzyme alkaline tolerance was also explored. Results: Recombinant pectate lyase (BspPel-th) showed the highest activity at 60°C and pH 11.0, and showed significant stability over a wide pH range (3.0–11.0). The specific enzyme activity after purification was 139.4 U/mg, which was 4.4 times higher than that of the wild-type enzyme. BspPel-th has good affinity for apple pectin, since the Vmax and Km were 29 μmol/min. mL and 0.46 mol/L, respectively. Molecular dynamics simulation results showed that the flexibility of the loop region of BspPel-th was improved. Conclusion: The modified BspPel-th has considerable potential for industrial applications with high pH processes.